Low-Complexity Belief Propagation detector for OTFS System - Zhang, Yang; Zhang, Qunfei; He, Chengbing; Ma, Meiling; Wang, Yingjie (2021 IEEE International Conference on Signal Processing, Communications and Computing (ICSPCC), 2021)
The orthogonal time frequency space (OTFS) modulation has emerged as a potential candidate modulation scheme for high mobility wireless communications. However, the matrix-inversion based detectors have prohibitively high complexity in OTFS systems due to high-dimensional channel matrix. In this paper, a low complexity belief propagation (BP) detection algorithm is therefore proposed for OTFS modulation over delay-Doppler channels. Specifically, the sparse feature of the equivalent channel matrix and the approximate probability update scheme are utilized to reduce computational complexity. In addition, we also add a damping factor to improve the convergence of the proposed algorithm, which brings substantial performance. Numerical simulation results that the proposed detection scheme effectively improves the bit error rate (BER) performance for OTFS systems.